An Analysis Of The Psychosocial Risk Factors At The Work Place That Cause Family Disintegration: The Case Of A Textile Company - Harumi Parra-Sanchez; María Eugenia Ciofalo-Lagos; Manuel Gonzalez-Perez (European Scientific Journal, ESJ, 2016)
It can be said that family is the foundation of every society. It is an intermediate institution in which values are learned. Also, it is the ideal environment to make progress and improve personal and professional capabilities, giving priority to human development and generating upstanding citizens that can survive in any environment. Therefore, the purpose of this research is to explore how it affects rotating shifts-to-family relationship and vice versa. Furthermore, this research intends to discover how to foster a better relationship among workers, their jobs, and their families. This is done by exploring and learning more about this problem. It is assumed that the shift rotation is a psychological factor that affects employees and fosters conflict between family and employment. Therefore, there is a precise definition of both, which is based on how couples under this scheme get along. This research was carried out in a textile company in Puebla City. The study subjects, who were workers, were chosen out of the four work shift options available at the business. For best results, the sample was formed with the convenience of the subjects in mind, taking the married ones who were cohabiting under these circumstances and who had at least one son.